Postmarketing safety evaluation of belimumab: a pharmacovigilance analysis - Huqun Li; Wenlong Xie; Chongshu Wang; Cuilian Guo (Lupus Science and Medicine)
Objective The present study aimed to provide a comprehensive evaluation of the postmarketing safety of belimumab based on the Food and Drug Administration Adverse Event Reporting System (FAERS) database.Methods Adverse event (AE) reports in the FAERS database from January 2021 to December 2023 were extracted to perform the disproportionality analysis by calculating the reporting OR. The clinical characteristics and onset times of AEs were investigated. The differences across ages and regions in belimumab-related AEs were also explored.Results A total of 4 974 201 AE reports were retrieved from the FAERS database, among which 9782 reports were related to belimumab. 485 positive safety signals related to belimumab were identified. In addition to the labelled AEs, such as depression and infections, new unexpected AEs, including product dose omission issue and inappropriate schedule of product administration, were identified. The median onset time of belimumab-related AEs was 75 days. Moreover, our analysis revealed frequently reported AEs in paediatric patients, such as systemic lupus erythematosus, and in adult patients, such as injection site pain. Additionally, AEs such as drug ineffective were commonly reported in patients of North America, Asia and Europe, while AEs, including an inappropriate schedule of product administration, had a high incidence in patients of South America.Conclusion The current study provides a valuable evaluation of the postmarketing safety of belimumab. Further studies are required to validate and confirm these findings. Clinicians should be vigilant regarding these potential AEs and pay more attention to the proper dosage regimen of belimumab in clinical practice.